(untitled) (Journal of the College of Education for Women, 2019)
Censure in poetry is a pattern of poetic construction, in which the poet evokes a voice other than his own voice or creates out of his own self another self and engages with him in dialogue in the traditional artistic style whose origin remains unknown. Example of the same may be found in the classical Arabic poets’ stopping over the ruins, crying over separation and departure and speaking with stones and andirons; all in the traditional technical mould. Censure confronting the poet usually emanates from the women as blaming, censure and cursing is closer to woman’s hearts than to the man’ hearts. Censure revolves around some social issues, such as the habit of over drinking wine and extravagant generosity taking risks, traveling, leaving home country and ageing etc.Classical poets have insisted on these topics and have frequently used them in their compositions. One such fact doing the rounds is that women love money and they are eager to sacrifice everything for the sake of money.The disobedience of the censurer is something the poets have been proud about, and they have stated the same in many places. Their disobedience to their censurers is a proof of their staunch faith in their thoughts and their pride in their own behave or.The censurer represents a rejection of something, or social practice facing the objection of other voice or expression of the pot’s philosophy on the issues of death and life; the poet always complaining about this censure gets fed up with it and refuses to surrender to him, the censurers follow the youth although the youth does not hear and urges his companions to disobey the censurers.In the same way as the Jahili poets followed this technical tradition, the mukhadram poets also followed suit, they remained beholden to it even the arrival of Islamic dawah could not turn them away from it and could not deter them from following in the footsteps of the first generation of poets in their compositions. We see Hassan bin Thabit, the poet of Prophet Mohammad (Peace be upon him) going on without any hesitation in diversification of the styles of his poems even while defending Islam and defending the Prophet and attacking the Quraish tribe.This is the traditional legacy which was keenly pursued by Hassan and the poets of his generation and other mukhadram poets who followed completely in the footsteps of their forefathers in their themes, styles and ways of composition.The present paper will dwell in some detail on one of the phenomena of Jahili Arabic poetry which has hitherto not received much attention i.e. the phenomenon of censure. The study aims to take a peep into the magical world of Jahili poetry to identify some of its hidden aspects and bring them out for all. We pray to Almighty Allah to help me achieve this goal.